Two differential equations;
f ′ ( x ) = − f 2 ( x ) + g 2 ( x ) f ( x ) .
g ′ ( x ) = 1 − ( f 2 ( x ) + g 2 ( x ) g ( x ) .
if g ( 0 ) = 0 and f ( 0 ) = 1 0 0 0 .
when ψ → ∞ f ( ψ ) = 0
What's g ( ψ ) ?
Moustafa could solve it! like!
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good Solution
f ′ ( x ) g ′ ( x ) = f ( x ) g ( x ) − f 2 ( x ) + g 2 ( x )
d f ( x ) d g ( x ) = f ( x ) g ( x ) − f 2 ( x ) + g 2 ( x )
using u = f ( x ) g ( x ) so
d g ( x ) = u d f ( x ) + f ( x ) d u
when you separate yields:
f ( x ) d f ( x ) + u 2 + 1 d u = 0
by integrating we yield that:
l n ∣ f ( x ) ∣ + l n ∣ u + u 2 + 1 ∣ = C 1
so g ( x ) + f 2 ( x ) + g 2 ( x ) = e 1 C
while g ( 0 ) = 0 and f ( 0 ) = 1 0 0 0 hence e 1 C = 1 0 0 0
when s → ∞
g ( s ) + f 2 ( s ) + g 2 ( s ) = 1 0 0 0
while f ( s ) = 0 when S → ∞
g ( s ) + 0 + g 2 ( s ) = 1 0 0 0 → g ( s ) = 2 1 0 0 0 = 5 0 0 .
انت بتاكلو
Problem Loading...
Note Loading...
Set Loading...
Multiplying f ( x ) and g ( x ) to differential equations f ′ ( x ) = f 2 ( x ) + g 2 ( x ) − f ( x ) and g ( x ) = 1 − f 2 ( x ) + g 2 ( x ) g ( x ) respectively.
Now adding both the equations we get f ( x ) f ′ ( x ) + g ( x ) g ′ ( x ) = g ( x ) − f 2 ( x ) + g 2 ( x ) f 2 ( x ) + g 2 ( x )
Simplifying it we get f ( x ) f ′ ( x ) + g ( x ) g ′ ( x ) = g ( x ) − f 2 ( x ) + g 2 ( x )
Dividing both side by f 2 ( x ) + g 2 ( x ) we get f 2 ( x ) + g 2 ( x ) f ( x ) f ′ ( x ) + g ( x ) g ′ ( x ) = − ( 1 − f 2 ( x ) + g 2 ( x ) g ( x ) )
Substituting g ′ ( x ) in the above equation and integrating both sides we get f 2 ( x ) + g 2 ( x ) = c − g ( x ) where c is a constant.
Now putting x = 0 in the above equation we get the value of c . Then putting ( ψ → ∞ ) in the above equation we get the value of g ( ψ ) which is equal to 5 0 0